A new drying approach deploying solid-solid phase change material: A numerical study. (1st October 2021) - Nejad, Alireza Mahdavi
Abstract: Recently, phase change materials are emerging in thermal drying technology. This study offers a new approach in thermal drying of a moist paper sheet deploying solid-solid phase change material, tentatively as an alternative to solid-liquid micro-encapsulated PCMs uniformly dispersed inside the void part of porous sheet. In contrast to SL-MEPCM scenario, SS-PCM is fabricated in solid matrix of porous medium, remaining the sheet porosity intact. Additionally, comparing to its SL-MEPCM counterpart, any costly PCM encapsulation process or change in the design of headbox of commercial paper machine is avoided. As well, volume change during phase transition is negligible. This configuration is particularly ideal for drying applications where a low porosity, initially highly moist sheet is to be dried. A numerical experiment is carried out to investigate the dewatering behavior of SS-PCM fabricated paper in a drying process. A real shape-stabilized polymeric SS-PCM is used in this study. A pattern search optimization technique is employed to minimize the target moisture content. This study shows SS-PCM primarily becomes effective in last stage of drying where it internally releases the heat gained in previous stages. The numerical results indicate the moisture removal is enhanced by approximately 29% utilizing SS-PCM. The effect of SS-PCM volume percentage and particularly infrared emitters are studied, as well. It is observed that SS-PCM equipped paper does not perform effectively in drying sectors where IR emitters are retrofitted. Eventually, a comparative study is performed to fairly compare the thermal performance of SL-MEPCM and SS-PCM in paper drying. Highlights: A new thermal drying approach utilizing solid-solid PCM is introduced. In contrast to SL-PCM scenario sheet porosity remains intact in this configuration. Drying rate is significantly improved employing a real polymeric solid-solid PCM. Low porosity initially highly moist material is ideal for this drying application. Solid-solid PCM performance alternates amid heat source and heat sink repeatedly.